Q: Simplify 6x - 2x - y6x - 2x - 2y 4x - 2y?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

(4x)(2y) would be factored as such: 4x = 2 â€¢ 2 â€¢ x 2y = 2 â€¢ y 2(2x)(y)

4x+2y = 6 2y = -4x+6 y = -2x+3 Perpendicular slope is 1/2

4x + 3y - 2x - 7y2x - 4y

If you mean: 2y = -4x-12 then y = -2x-6 and -6 is the y intercept

Simplify 4x + 3 = 2x + 8 2x = 5 x =2½

Related questions

6x-2y

the answer to this problem is -2x^2y^2

(4x)(2y) would be factored as such: 4x = 2 â€¢ 2 â€¢ x 2y = 2 â€¢ y 2(2x)(y)

4x + 2y = -8 → 2y = -4x - 8 → y = -2x - 4

2y = 4x + 4y = 2x + 2

4x + 2y = 20 2y = -4x + 20 y = -2x + 10.......but you may also write it as y = 10 - 2x.

4x+2y=24 => 2y=24-4x => y=12-2x and the slope is -2

4x+2y = 20 2y = -4x+20 y = -2x+10

4x2 - 4x + 2xy - 2y = 4x(x - 1) + 2y(x - 1) = (x - 1)(4x + 2y) = 2(x - 1)(2x + y)

-4x-2y = 3 -2y = 4x+3 y = -2x-1.5 which is the equation of a straight line

4x-2y = 3 -2y = -4x+3 y = 2x-1.5 in slope intercept form

2y = 6 4x y=3 + 2x y= 2x + 3